The Analysis of the Factors Contributing to EFL Student's Difficulties in Finishing English Undergraduate Thesis - Khusniyah, Zalfa Armiah; Ismiatun, Febti (LET: Linguistics, Literature and English Teaching Journal, 2024)
This research aims to analyze the factors contributing to students’ difficulties in writing an undergraduate thesis. The researcher used Narrative Inquiry as the research approach in this qualitative research. The participant was an 11th-semester student of the English Education department at one of the universities in Malang, Indonesia. The researcher conducted a direct Interview with open-ended questions to gain the data. This finding shows four significant factors that affect an undergraduate student in finishing the undergraduate thesis: psychological factors, English linguistic factors, English Proficiency factors, and student attitude factors. Considering the findings, the researcher suggested some solutions in the following: Improve English linguistic ability; improve English speaking proficiency; organize time effectively; build communication with the supervisor; and read many references.